Development and validation of the Stimulant Refusal Self-Efficacy Questionnaire (SRSEQ) in stimulant users in treatment. (1st November 2021) - Wanigasooriya, Angela; Connor, Jason P.; Young, Ross McD.; Feeney, Gerald F.X.; Gullo, Matthew J.
Abstract: Background: Self-efficacy is a core component of Social Cognitive Theory. Refusal self-efficacy is an individual's belief in their ability to refuse a substance in specific high-risk situations. Change in refusal self-efficacy is predictive of positive treatment outcomes. Measurement of refusal self-efficacy is critical as it directs coping skills development techniques though existing behavioural treatments. There is no validated measure of stimulant refusal self-efficacy. This study developed and validated the Stimulant Refusal Self-Efficacy Questionnaire (SRSEQ) to measure confidence in the ability to refuse stimulants in specific high-risk situations. Method: Two hundred and seven stimulant-using patients referred for assessment completed the SRSEQ and measures including stimulant dependence severity (Severity of Dependence Scale-Stimulant, SDS-S). Confirmatory Factor Analysis (CFA) using structural equation modelling (SEM) was conducted to test the theoretically-driven three-factor structure of the SRSEQ. Criterion validity was tested with severity of stimulant dependence. Results: The CFA supported the three-factor structure. Emotional Relief (β = −0.27, p  = .008), Opportunistic (β = −0.24, p  = .013) and Social Facilitation (β = −0.32, p  < .001) refusal self-efficacy were uniquely associated with stimulant dependence severity, explaining 55.1% variance. Conclusions: The SRSEQ is psychometrically sound and may be clinically useful to assist with assessment and treatment planning for stimulant use disorder. Highlights: No validated stimulant refusal self-efficacy measure exists. SRSEQ showed good fit to data. Factor structure matches alcohol and cannabis self-efficacy. All SRSEQ scales uniquely predict dependence severity.